Sliding Mode Observer Design For Sensor Fault Diagnostic Of A Mechatronics System - Saidin, Muhammad Amirul Asyraf (Universiti Sains Malaysia, 2018)
Fault detection plays an important role in the manufacturing area as it can help the manufacturer to detect the faulty system earlier before it can affect the overall processes. Fault detection and compensation are even more crucial in an interconnected system, giving an examples of multi-robot manipulators are employed to perform cooperative task. Interconnectedness within the system which means each subsystem is depend on each other in order to do the task given, an estimation system must be deployed which can help to estimate the health of subsystem condition. In this project, a linear observer is studied at first and simulated under a noisy encoder feedback scenario. The study is further extended to the formulation of robust nonlinear observer utilizing the theory of sliding mode. The state-space model representing the dynamic of the studied DC motor is transformed first into a nominal canonical form before the robust nonlinear observer is designed. The fault type introduced in an encoder sensor feedback is in a form of white Gaussian noise (bounded). Simulation of the robust nonlinear observer in reconstructing the corrupted sensor feedback rereads the successful convergence to the true position value. This is further supported by experimentation using the real DC motor which is equipped with an encoder. The fault is introduced via hardware-in-the-loop concept using Simulink block set.